Zero Waste Lifestyle as an Effort to Reduce Waste From Its Source - Hidayati, Nanik Hidayati, (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
The issue of waste increasingly threatens life in the biosphere, both on land and in water bodies. The accumulated waste collected each year forms massive piles. Waste that is burned causes air pollution and produces greenhouse gases, contributing to global warming and ozone depletion. Various methods, including recycling, have been implemented, yet only 20% of waste is successfully recycled. Therefore, it is necessary to make efforts to reduce waste at its source by educating people about a zero-waste lifestyle. This research is a qualitative study with data collected from interviews, documentation, participatory observation, and literature review. Additionally, questionnaires were used to obtain the zero-waste index percentage and to complement the data. The research subjects include the community and the KerDUS Community in Kendal Regency, Indonesia. The community actively engages in educating the public about zero waste. The community prepares trainers and mentors to provide environmental awareness materials and training on recycling used goods. The community's slogan "Zero Waste Konco Resikan" inspires members to continually share their knowledge. The divisions involved in waste management include POC Konco Resikan, eco-enzyme, ecobrick, maggot gazebo, florist, Mijel soap, bioactivator, Bungpi lampion, compost, and fabric mats. Trained individuals are expected to practice these methods at home.